PENGARUH MENDENGARKAN MURATTAL AL QURAN TERHADAP PENINGKATAN KEMAMPUAN KONSENTRASI - Very Julianto; Rizki Putri Dzulqaidah; Siti Nurina Salsabila (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2014)
The study aimed to determine the effectiveness of listening murattal Al Qur’an in increasing concentration capability. Subjects in this study were the girls students of Universitas Islam Negeri Sunan Gunung Djati Bandung, 18-20 years old, with GPA is above 3,00. The measurement of this study is using Digit Span test. The data were analyzed by using a statistical parametric T test. The mean score of concentration gained by the experimental group subjects before treatment was10,4, and after treatment was 11,2. While the mean score of the control group subjects before treatment was 11, and after treatment was 11,4. The result can be interpreted that there was mean differences between the experimental group and the control group before and after treatment. It means that listening murattal is effective in increasing the capability of concentration.